Pengaruh Psychological Capital, Perceived Organizational Support dan Job Enjoyment terhadap Intensi Job Hopping pada Karyawan Generasi Y di Kota Kudus - Fahira, Keke Tamara; Septanti, Annisya Lutfi (STIE AMKOP, 2025)
The phenomenon of high job mobility or job hopping, especially among generation Y (millennial) employees, is a major challenge for HR management. Although various studies have examined each of these variables separately, there is still limited research that comprehensively tests the simultaneous influence of psychological capital, perceived organizational support, and job enjoyment on job hopping intentions, especially among generation Y employees in Kudus City. Therefore, this study aims to fill this gap by investigating how these three variables together influence the decision of generation Y employees to change jobs. Multiple linear regression analysis was used in this study using SPSS. Respondents were Generation Y employees in Kudus Regency. The sampling technique used purposive sampling technique, namely Generation Y active employees and work experience in more than 1 company. Number of samples 114 respondents. The analysis techniques used were validity test, reliability test, normality test, hypothesis test, simultaneous test, and coefficient of determination test (R2). The results of this study on the Psychological Capital variable have a negative and significant effect on Job Hopping. Perceived Organizational Support has a negative and significant effect on Job Hopping. Job Enjoyment has a negative and significant effect on Job Hopping. The conclusion in this study is that Psychological Capital, Perceived Organizational Support and Job Enjoyment partially or simultaneously have a negative effect on Job Hopping of Generation Y Employees. Based on the findings of the study, the company should improve communication and transparency with employees. Provide awards and recognition for employee contributions. Provide support in career development and employee welfare